PENGARUH PENJUALAN DAN PERPUTARAN PERSEDIAAN TERHADAP PERTUMBUHAN LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BEI PERIODE 2013-2017 - Ghonimah Zumroatun Ainiyah (Medikonis, 2020)
ABSTRACT This study aims to explain the effect of sales and inventory turnover on earnings growth with firm size as an intervening variable. This study took the the automotive companies listed on the Indonesia Stock Exchange in the period 2013-2017 as the object. This research was a quantitative research. The data used in this study was secondary data, the population in this study was the automotive company that listed on the Indonesia Stock Exchange in the period 2013-2017. The sampling technique in this study was a sample purposive sampling and obtained 9 companies. Data analysis in this study used a mediating variable regression analysis with the causal step method with SPSS 16 software. The results of this study indicate that: 1) Sales had a negative and no significant effect on earnings growth. 2) Inventory turnover had a positive and significant effect on profit growth. 3) Sales had a negative and no significant effect on company size. 4) Inventory turnover had a positive and significant effect on company size. 5) Company size had a positive and significant effect on profit growth. 6) Sales had a negative and no significant effect on earnings growth with firm size as an intervening 7) Inventory turnover had a positive and significant effect on earnings growth with firm size as an intervening variable.